Uncover the Meaning of Figurative Language in BTS Selected Song Lyrics - Cahyani, Ni Putu Risma; Pratiwi, Desak Putu Eka; Maharani Santika, Dewa Ayu Devi (e-Journal of Linguistics; Vol 15 No 2 (2021): enDO - 10.24843/e-jl.2021.v15.i02.p11, 2021)
This article entitled "Uncover the Meaning of Figurative Language in BTS Selected Song Lyrics". Figurative language is language that have some meaning behind the word or sentence and uses figures of speech. A figure of speech could even be how of claiming something aside from the literal meaning of the world. This article aims to analyze the types of figurative language and uncover the meaning of figurative language used in BTS selected song lyrics. The writer is interested in analyzing BTS selected songs since their songs not only tell stories of love or heartbreak, but also about current social situation. The data were collected by observation method and note taking technique. The collected data were analyzed by descriptive qualitative method using theory proposed by Keraf (2006) and Kennedy (1983) to identify the types of figurative language and theory of meaning by Leech (1981) to uncover the meaning of figurative language. The finding shows that there are various figurative language used in BTS song lyrics such as metaphor, metonymy, hyperbole, symbol, and synecdoche.